Preclinical models of disease and multimorbidity with focus upon cardiovascular disease and dementia. (December 2020) - Shabir, Osman; Moll, Tobias A.; Matuszyk, Martyna M.; Eyre, Beth; Dake, Manmohi D.; Berwick, Jason; Francis, Sheila E.
Highlights: Animal models are useful in furthering our understanding of human disease mechanisms as well as identifying potential therapeutic targets, especially in the context of dementia. Diseases of ageing are often multi-systemic and present with additional comorbidities that are not fully recapitulated in the many of the animal models available. Combining animal models to incorporate comorbidities may be more useful if clinical trials are to pass successfully. Abstract: The use of animal models is fundamental to furthering our understanding of human disease mechanisms, as well as identifying potential therapeutic targets. Diseases of ageing often involve multiple body systems; however, multi-systemic features are not fully recapitulated in the many of the animal models available. Therefore, combining pre-clinical models to better reflect the multimorbidities observed at the clinical level is critical. This review will highlight some of the key pre-clinical experimental models associated with cardiovascular (atherosclerosis, coronary heart disease), cerebrovascular (stroke, vascular dementia), metabolic (obesity, type-2 diabetes mellitus) and neurological (amyotrophic lateral sclerosis, frontotemporal dementia, Parkinson's, epilepsy) diseases, and whether these models encompass known multimorbidities. In addition to this, we discuss established pre-clinical models that combine two or more conditions, within the context of dementia.